(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides an analysis of the problems of improving product quality in the construction and building industry enterprises, as well as methods of creating a system of rapid quality control. It also describes the types of preparations for the introduction of the system, the description of the final results of the control system, conclusions and recommendations.